Capacity for Cellular Osmoregulation Defines Critical Salinity of Marine Invertebrates at Low Salinity - Podbielski, Imke; Hiebenthal, Claas; Hajati, Mithra-Christin; Bock, Christian; Bleich, Markus; Melzner, Frank (Frontiers in Marine Science, 2022)
Low-salinity stress can severely affect the fitness of marine organisms. As desalination has been predicted for many coastal areas with ongoing climate change, it is crucial to gain more insight in mechanisms that constrain salinity acclimation ability. Low-salinity induced depletion of the organic osmolyte pool has been suggested to set a critical boundary in osmoconforming marine invertebrates. Whether inorganic ions also play a persistent role during low-salinity acclimation processes is currently inconclusive. We investigated the salinity tolerance of six marine invertebrate species following a four-week acclimation period around their low-salinity tolerance threshold. To obtain complete osmolyte budgets, we quantified organic and inorganic osmolytes and determined fitness proxies. Our experiments corroborated the importance of the organic osmolyte pool during low-salinity acclimation. Methylamines constituted a large portion of the organic osmolyte pool in molluscs, whereas echinoderms exclusively utilized free amino acids. Inorganic osmolytes were involved in long-term cellular osmoregulation in most species, thus are not just modulated with acute salinity stress. The organic osmolyte pool was not depleted at low salinities, whilst fitness was severely impacted. Instead, organic and inorganic osmolytes often stabilized at low-salinity. These findings suggest that low-salinity acclimation capacity cannot be simply predicted from organic osmolyte pool size. Rather, multiple parameters (i.e. osmolyte pools, net growth, water content and survival) are necessary to establish critical salinity ranges. However, a quantitative knowledge of cellular osmolyte systems is key to understand the evolution of euryhalinity and to characterize targets of selection during rapid adaptation to ongoing desalination.